Extreme degree of chromosome number variability in species of the spider genus Scytodes (Araneae, Haplogynae, Scytodidae) - Araujo, D. [UNESP]; Rheims, C. A.; Brescovit, A. D.; Cella, D. M. [UNESP] (Wiley-Blackwell, 2008)
Genus Scytodes includes most species of the spider family Scytodidae. Until now, 187 species of the genus have been described. In spite of this great diversity, only three Scytodes species were karyotyped so far. The present paper provides for the first time karyotype analysis of two synanthropic species, Scytodes fusca and Scytodes itapevi. Furthermore, new data on karyotype of Scytodes globula are also provided using conventional and differential cytogenetical procedures. The diploid number in the genus Scytodes varied considerably, namely from 2n = 13 to 2n = 31. The diploid number found in S. globula (2n male = 13) is the lowest in haplogyne spiders with monocentric chromosomes. Except S. globula, this number has been found only in one haplogyne spider with monocentric chromosomes, namely Ochyrocera sp. (Ochyroceratidae). on the contrary, the diploid number of S. fusca (2n male = 31) is one of the highest diploid numbers recorded in haplogyne spiders. The degree of intrageneric variation found in the genus Scytodes is the highest recorded in araneomorph spiders with monocentric chromosomes so far. Some karyotype characteristics (diploid number, chromosome morphology, total chromosome length, and distribution of constitutive heterochromatin) allowed us to postulate a close relationship between S. globula and S. itapevi. According to the karyotype data, S. fusca is not closely related to these two species. This conclusion corroborates a recent taxonomic work that grouped S. globula, S. itapevi, and other four Scytodes species in the 'globula group'.
Keywords: constitutive heterochromatin; meiosis; karyotype; sex chromosome system; Araneomorphae